Treatment of infective endocarditis caused by Enterococcus faecalis with a combination of penicillin G and ceftriaxone: a case report and literature review - Jiang, Li; Lin, Zhiqiang; Wu, Shuifa; Chen, Tingting (Frontiers in Cardiovascular Medicine, 2025)
This report presents a case of Infective Endocarditis (IE) caused by Enterococcus faecalis (E. faecalis). The E. faecalis isolates were sensitive to ampicillin, penicillin G, and vancomycin. However, the outcome of anti-infection therapy was poor, and the patient was suspected to be allergic to vancomycin and ampicillin-sulbactam. This prompted various changes in antibiotic treatment regimens, with the patient eventually cured after administration of penicillin G combined with ceftriaxone (PC regimen). Literature was retrieved from the CNKI, Wanfang, Weipu, and PubMed databases to determine the efficacy of the PC regimen in the treatment of E. faecalis-induced IE. From the literature retrieved and our case study, there were only five reports of cases that had been treated with the PC regimen, with a mean age of (61.6 ± 17.2) years. The cases that had been previously reported in the literature involved patients of advanced age with complicated underlying diseases such as chronic obstructive pulmonary disease (COPD), atrial valve replacement, bladder carcinoma, and type 2 diabetes mellitus. The minimal inhibitory concentration (MIC) of ampicillin against the E. faecalis isolates from all five patients was <2 μg/ml, and all isolates showed susceptibility to penicillin G. All five patients were initially treated with other antimicrobial regimens but were eventually cured after switching to the PC regimen. In conclusion, ampicillin combined with ceftriaxone (AC regimen) can be substituted with the PC regimen for the treatment of IE caused by penicillin-susceptible E.faecalis when ampicillin is not available, when outpatient parenteral antimicrobial therapy (OPAT) with an AC regimen is not feasible, or when the patient is allergic to ampicillin.